Mapping Kindergarten Students' Behaviour towards Use of Learning Space - Nugraha, Dian; Purnama, Muhammad Sega Sufia; Pratama, Mukhamad Risa Diki (International Journal of Built Environment and Scientific Research, 2024)
Sentra allow children to manipulate various objects, engage in role playing conversations with their friends, explore, interact physically, emotionally, socially and cognitively as well as other interesting varied activities. Sentra provide opportunities for children to play individually, in small or large groups and even classically. Children are allowed to choose activities that interest them and will eventually make children active and interactive learners. This research uses a descriptive qualitative method in the case of Al Azhar Kindergarten. The mapping results show that there is a tendency for students to use mattresses in carrying out activities. The lack of furniture makes students look for a comfortable position when doing activities. Space elements can create an atmosphere that suits the character of the child.  The use of soft foam mattresses as a base with bright colour can provide a sense of security because it suits the character of active children.